Fundamental aspects of Arn+ SIMS profiling of common organic semiconductors. (28th July 2014) - Fleischmann, C.; Conard, T.; Havelund, R.; Franquet, A.; Poleunis, C.; Voroshazi, E.; Delcorte, A.; Vandervorst, W.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; et al.
<x xml:space="preserve">Abstract</x> We investigate the capabilities and limitations of performing (quantitative) in‐depth composition analysis of polymer:fullerene blends, using time‐of‐flight SIMS with large Arn+ clusters. These blends constitute an important class of organic solar cell materials, whose performance and reliability critically depend on the blend's physicochemical properties at the nanoscale. We investigate the effect of Ar cluster size n, kinetic energy E and E/n on the secondary ion and sputter yields and evaluate the Ar beam‐induced damage in these layers. On the basis of this, the ideal experimental conditions are derived that allow us to investigate matrix effects and variations in sputter yields as function of polymer:fullerene compositions. We demonstrate that time‐of‐flight SIMS is capable to retrieve quantitative in‐depth information in common polythiophene, polycarbazole, and fullerene blends. Copyright © 2014 John Wiley & Sons, Ltd.